Peran SCM terhadap Keputusan Pembelian Ritel Konvensional (Toko Madura) di Bojonegoro - Cahya, Kevin Dwi Nur; Anggapratama, Reza; Irnawati, Dwi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the influence of Supply Chain Management (SCM) dimensions, including Delivery Information Management, Quality Control, and Customer Relationship, on purchasing decisions in conventional stores (Toko Madura) in Bojonegoro. The research is motivated by the crucial role of SCM in enhancing the competitiveness of traditional retail businesses amid the dominance of modern retail and e-commerce. A quantitative descriptive approach, with 100 consumer respondents conventional stores (toko madura) in Bojonegoro. The results indicate that Quality Control and Customer Relationship have a significant effect on purchasing decisions, while Delivery Information Management shows no significant effect. Simultaneously, the three SCM dimensions significantly influence purchasing decisions, with a determination coefficient value of 61.5%. These findings highlight the importance of improving product quality and customer relationships as key strategies for conventional retailers to maintain customer loyalty and enhance competitiveness in the digital era.